The path for innovative severe accident neutronics studies in ZPRs. part I.2 - Interpretation of SNEAK-12A experiment for core disruption in LMFBRs impact of nuclear data uncertainties on reactivity coefficients. (April 2017) - Margulis, M.; Blaise, P.; Mellier, F.; Gilad, E.
Abstract: The present work details a further investigation of the SNEAK-12A experimental program, which aimed to study material relocation in Sodium Fast Reactors (SFRs) leading to core degradation. The further investigation include sensitivity and uncertainty propagation analysis. In this paper, a comparison is made using two codes, a Monte Carlo based code Serpent 2 and the deterministic system code ERANOS. A sensitivity analysis was made utilizing the two codes, with comparison of two nuclear data libraries (ENDF/B-VII.1 and JEFF-3.1.1). The code-to-code comparison resulted in a very good agreement, while the comparison of libraries showed large discrepancies, manly due to the differences in the sodium cross-section data. The sensitivity analysis, was followed by a complete propagated uncertainty analysis based on the covariance evaluated data available in the COMAC data evaluation. The results of the uncertainties show that there are still large discrepancies linked to the nuclear data. This work is done within the frame work of new core design capacities and new ways of conducting in Zero Power Reactors, such as the ZEPHYR project led independently by CEA.